Diabetes Self Management Education Assistance on The Quality of Life in Type 2 Diabetes Mellitus Patients - Buana, Chandra; Tarwoto, Tarwoto; Retnaningtyas, Ekowati; Harmonis, Rita; Sridiany, Sridiany (Riviera Publishing, 2023)
Patients with DM in the district. Rejang Lebong reached 382 cases, and 9 people died from this disease in 2020. Diabetes Self Management Education (DSME) is a program designed to provide understanding and skills in caring for DM sufferers daily at home. This subject of this study was to analyze the effect of DSME administration on the quality of life in type 2 DM patients in the PKM Perumnas area, Rejang Lebong district. This research is a quasi-experimental study with a pretest and posttest approach with a control group design. The sampling technique used consecutive sampling involving 30 respondents, divided into 15 respondents in the treatment group and 15 in the control group. Bivariate analysis in the form of a parametric test, namely the dependent t-test and independent t-test with ? = 0.05. Researchers use computer programs for data processing and statistical analysis. The mean quality of life for DM patients was 36.20 with a standard deviation of 10.79 and p = 0.000 <0.05. This shows that after the intervention, there is an increase in the quality of life of DM patients by 36.20. There is an effect of Diabetes Self-Management Education (DSME) on the Quality of Life of Diabetes Mellitus (DM) Patients in Kab. Rejang Lebong in 2022. Education is essential for patients to change their behaviour and self-management independently to improve the quality of life of DM patients.